Infliximab in combination with methotrexate in active ankylosing spondylitis: a clinical and imaging study. Issue 11 (13th April 2005) - Marzo-Ortega, H; McGonagle, D; Jarrett, S; Haugeberg, G; Hensor, E; O'Connor, P; Tan, A L; Conaghan, P G; Greenstein, A; Emery, P
Abstract : Objective: To examine the efficacy and safety of infliximab combined with methotrexate compared with methotrexate alone in the treatment of ankylosing spondylitis (AS) using MRI and DXA to monitor its impact on bone. Methods: In this single centre study 42 subjects with active AS were treated with methotrexate and were randomly assigned, in a ratio of 2:1, to receive five infusions of either 5 mg/kg infliximab or placebo over 30 weeks. The primary outcome was improvement in disease activity as shown by the BASDAI at week 30. MRI was used to assess the effect of treatments on sacroiliac and spinal enthesitis/osteitis and DXA to monitor bone mineral density. Results: Both therapeutic agents were well tolerated with no dropouts due to adverse events. A significantly greater improvement in mean BASDAI score was seen in the infliximab arm at week 10 (p = 0.017) than in the placebo arm, but this was not maintained by week 30 (p = 0.195), 8 weeks after the last infusion, at which stage disease flares were reported by some subjects. MRI showed that the mean number of lesions resolving for each subject from week 0 to week 30 was significantly greater in the combination group than in the methotrexate monotherapy group (p = 0.016). Conclusions: Infliximab in combination with methotrexate was a safe and efficacious treatment in AS over 6 months and was associated with significant regression in enthesitis/osteitis as determined by MRI. However, disease flares were reported 8 weeks after the last infusion, indicating that addition of methotrexate failed to extend the infliximab dosing interval.